Plasma lipidomic analysis to investigate putative biomarkers of P‐glycoprotein activity in healthy volunteers - Théodore Decaix; Romain Magny; Isabelle Gouin‐Thibaut; Xavier Delavenne; Patrick Mismetti; Joe‐Elie Salem; Céline Narjoz; Anne Blanchard; Marion Pépin; Nicolas Auzeil; Marie‐Anne Loriot; Olivier Laprévote (Wiley, 2023)
Abstract P‐glycoprotein (P‐gp) is an efflux transporter involved in the bioavailability of many drugs currently on the market. P‐gp is responsible for several drug-drug interactions encountered in clinical practice leading to iatrogenic hospital admissions, especially in polypharmacy situations. ABCB1 genotyping only reflects an indirect estimate of P‐gp activity. Therefore, it would be useful to identify endogenous biomarkers to determine the P‐gp phenotype to predict in vivo activity prior to the initiation of treatment and to assess the effects of drugs on P‐gp activity. The objective of this study was to assess changes in plasma lipidome composition among healthy volunteers selected on the basis of their ABCB1 genotype and who received clarithromycin, a known inhibitor of P‐gp. Untargeted lipidomic analysis based on liquid chromatography-tandem mass spectrometry was performed before and after clarithromycin administration. Our results revealed changes in plasma levels of some ceramides (Cers) {Cer(d18:1/22:0), Cer(d18:1/22:1), and Cer(d18:1/20:0) by ~38% (p < 0.0001), 13% (p < 0.0001), and 13% (p < 0.0001), respectively} and phosphatidylcholines (PCs) {PC(17:0/14:1), PC(16:0/18:3), and PC(14:0/18:3) by ~24% (p < 0.001), 10% (p < 0.001), and 23.6% (p < 0.001)} associated with both ABCB1 genotype and clarithromycin intake. Through the examination of plasma lipids, our results highlight the relevance of untargeted lipidomics for studying in vivo P‐gp activity and, more generally, to safely phenotyping transporters.